Control Theory Concepts Applied to Retail Supply Chain: A System Dynamics Modeling Environment Study. (20th November 2013) - Janamanchi, Balaji; Burns, James R.
Abstract : Control theory concepts have been long used to successfully manage and optimize complex systems. Using system dynamics (SD) modeling methodology, which is continuous deterministic simulation modeling methodology, we apply control theory concepts to develop a suitable performance functional (or objective function) that optimizes the performance of a retail supply chain. The focus is to develop insights for inventory management to prevent stock-outs and unfilled orders and to fill customer orders at the lowest possible cost to supply chain partners under different scenarios, in a two-player supplier-retailer supply chain. Moderate levels of inventory, defining appropriate performance functional, appear to be crucial in choosing the right policies for managing retail supply chain systems. The study also demonstrated how multiple objectives can be combined in a single performance functional (or objective function) by carefully assigning suitable weights to the components of objectives based on their priority and the existence of possible trade off opportunities.